The effects of nursing care package implementation on pressure injuries prevention in the intensive care unit - Sevda Önen; Özlem Doğu (BMC Nursing)
Abstract Aim The study was aimed to evaluate the effect of the care package prepared in accordance with the algorithm in the intensive care unit on the prevention of pressure injuries. Background Pressure injuries are frequently encountered in intensive care units and negatively affect the treatment process and recovery. Design The study was planned a retrospective and quasi-experimental design. Methods The study consisted of two stages. First; development of the care package, nursing education for the use of the developed care package, and implementation of the care package. Second; to evaluate the effectiveness of the care package by comparing the incidence of pressure injuries in the intervention group (December 2019-April 2020) and the control group (May-September 2019) in the pre-study period. The study was conducted with a total of 80 patients hospitalised in the general intensive care unit. The control group (n = 40) was selected retrospectively and had the same characteristics as the intervention group (n = 40). Results The findings revealed that the proportion of individuals who developed a pressure injury was higher in the control group as of the 7th day. Pressure injuries developed in 8.52 ± 3.24 days in the control group and 11.00 ± 2.21 days in the intervention group (p < 0.05). The incidence rate of pressure injuries was calculated to be 30.43% in the pre-algorithm period and 17.5% in the period during which the algorithm was applied. There was a significant difference in the incidence rates of pressure injuries (p < 0.05) between the two periods. Conclusions Adopting evidence-based practice and using care packages prepared accordingly enables nurses to be successful in improving the quality of care. This also contributes to the prevention of pressure injury formation and health costs.